Sex-related differences in the presentation, treatment and outcomes among patients with acute coronary syndromes: the Global Registry of Acute Coronary Events. Issue 1 (7th May 2008) - Dey, S; Flather, M D; Devlin, G; Brieger, D; Gurfinkel, E P; Steg, P G; FitzGerald, G; Jackson, E A; Eagle, K A; ,
Abstract : Objective: To assess whether sex differences exist in the angiographic severity, management and outcomes of acute coronary syndromes (ACS). Methods: The study comprised 7638 women and 19 117 men with ACS who underwent coronary angiography and were included in GRACE (Global Registry of Acute Coronary Events) from 1999–2006. Normal vessels/mild disease was defined as <50% stenosis in all epicardial vessels; advanced disease was defined as ⩾one vessel with ⩾50% stenosis. Results: Women were older than men and had higher rates of cardiovascular risk factors. Men and women presented equally with chest pain; however, jaw pain and nausea were more frequent among women. Women were more likely to have normal/mild disease (12% vs 6%, p<0.001) and less likely to have left-main and three-vessel disease (27% vs 32%, p<0.001) or undergo percutaneous coronary intervention (65% vs 68%, p<0.001). Women and men with normal and mild disease were treated less aggressively than those with advanced disease. Women with advanced disease had a higher risk of death (4% vs 3%, p<0.01). After adjustment for age and extent of disease, women were more likely to have adverse outcomes (death, myocardial infarction, stroke and rehospitalisation) at six months compared to men (odds ratio 1.24, 95% confidence interval 1.14 to 1.34); however, sex differences in mortality were no longer statistically significant. Conclusions: Women with ACS were more likely to have cardiovascular disease risk factors and atypical symptoms such as nausea compared with men, but were more likely to have normal/mild angiographic coronary artery disease. Further study regarding sex differences related to disease severity is warranted.